Reusable Nanocomposite Membranes for Highly Efficient Arsenite and Arsenate Dual Removal from Water - Hugo Salazar; Pedro Manuel Martins; Ainara Valverde; Roberto Fernández de Luis; José Luis Vilas‐Vilela; Stanislav Ferdov; Gabriela Botelho; Senentxu Lanceros‐Mendez (Advanced Materials Interfaces, 2022)
Abstract Nanocomposite membranes (NCMs) of poly(vinylidene fluoride‐hexafluoropropylene), PVDF‐HFP, with different yttrium carbonate and magnetite loadings, are prepared, and their dual adsorption capacity over neutral arsenite and anionic arsenate species is evaluated. The nanoparticles (NPs) and the corresponding NCMs are fully characterized in morphology, microstructure, thermal, and surface properties. The nanocomposite membranes present a micrometric porous structure with a homogeneous distribution of the active nanoparticles. Chemical, thermal, and water‐contact angle characteristics of the NCMs point out that they maintain the chemical and thermal stability of the polymer while improving the wettability. Arsenic removal depends on NP loading and pH of the media. For instance, efficiencies close to 100% are achieved for arsenate species under acidic conditions, while adsorption capacity over arsenite is also incremented above 80%. Fe3O4/PVDF‐HFP nanocomposite shows a dual affinity for the adsorption of As(III) and As(V) species, with the maximum adsorption capacities of 92.82 and 137.08 mg g−1, respectively. In addition, both NCMs are easily activated and reused without significant efficiency loss. Consequently, the nanocomposite membranes represent low‐cost, reusable, and efficient water remediation systems suitable for the long‐term removal of As(III) and As(V) under conditions mimicking real polluted surface and groundwater.